2022
DOI: 10.1128/spectrum.01436-21
|View full text |Cite
|
Sign up to set email alerts
|

FAdV-4 without Fiber-2 Is a Highly Attenuated and Protective Vaccine Candidate

Abstract: Among all serotypes of fowl adenovirus, serotypes FAdV-1, FAdV-4, and FAdV-10 are unique members with two fiber genes ( fiber-1 and fiber-2 ). Recent studies reveal that Fiber-1, not Fiber-2, directly triggers viral infection of FAdV-4, whereas Fiber-2, but not Fiber-1, has been identified as the major virulence determiner and an efficient protective immunogen for subunit vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…Their results showed that hexon, but not fiber-2, determines the virulence of the novel FAdV-4 strain and identified hexon residue 188 as the key amino acid for the virulence of the Chinese epidemic FAdV-4 strain ( 17 ). This result conflicts with previous research findings that both hexon and fiber-2 are closely associated with the virulence of the Chinese FAdV-4 strains, such as HNJZ and SD ( 12 , 15 , 24 ). Actually, the genome sequence identity between FAdV-4 strains HLJFAd15 (GenBank accession no.…”
Section: Discussioncontrasting
confidence: 99%
“…Their results showed that hexon, but not fiber-2, determines the virulence of the novel FAdV-4 strain and identified hexon residue 188 as the key amino acid for the virulence of the Chinese epidemic FAdV-4 strain ( 17 ). This result conflicts with previous research findings that both hexon and fiber-2 are closely associated with the virulence of the Chinese FAdV-4 strains, such as HNJZ and SD ( 12 , 15 , 24 ). Actually, the genome sequence identity between FAdV-4 strains HLJFAd15 (GenBank accession no.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the birds analyzed in this study were not vaccinated, so it can be deduced that the viral strains that are present in commercial batches are field strains. Many studies showed that the genotypes characterized here were associated with outbreaks of IBH or HHS in chickens in several countries around the world [ 41 , 46 , 47 , 48 ]; however, the vast majority of reports of IBH or HHS worldwide have been associated with FAdV-4/C1 [ 23 , 49 , 50 , 51 , 52 ] and the report of a large number of outbreaks associated with this FAdV genotype has led many studies to focus on the development of vaccines based on this viral genotype [ 53 , 54 , 55 ], as well as associations with other genotypes (FAdV-8b/E3) where excellent protection against infections with both genotypes is shown [ 1 , 12 , 56 , 57 , 58 ]. However, these recombinant vaccines have not been tested with other FAdV genotypes that are included in the same group to which the vaccine strains belong, in the case of FAdV-8b/E3 belonging to species E, perhaps it could generate protection against FAdV-8a/E2 and FAdV-6/E1 strains and be an alternative in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that Fiber-1 of FAdV-4 directly triggered the viral infection via its shaft and knob domains and Fiber-2 of FAdV-4 was identified as a major virulent determiner (Wang et al, 2020). More recently, we found that Fiber-2 of FAdV-4 was not necessary for viral replication and induction of neutralizing antibody, and fiber-2-edited or fiber-2-deleted FAdV-4 was a highly attenuated and protective vaccine candidate (Xie et al, 2021;Xie et al, 2022), highlighting that fiber-2 can be as an editable or inserting site for generating live-attenuated recombinant FAdV-4 vaccines against both FAdV-4 and other pathogens. In this study, the fiber-2 gene in FAdV-4 was replaced with the fiber-2 gene of DAdV-3 to generate a fiber-2-edited recombinant FAdV-4 expressing the fiber-2 gene of DAdV-3 through CRISPR/Cas9 and Cre-LoxP systems.…”
Section: Discussionmentioning
confidence: 99%